Cerebral correlates of autobiographical memory in MCI and AD: Evidence from a positron‐emission tomography study: Developing topics. (7th December 2020) - Frankenberg, Claudia; Schröder, Johannes; Haberkorn, Uwe; Degen, Christina; Buchsbaum, Monte S.
Abstract: Background: Autobiographical memory (AM) changes are the hallmark of Alzheimer's disease (AD) and Mild Cognitive Impairment (MCI). In recent neuroimaging studies, AM changes were associated with numerous cerebral sites, such as the frontal cortices, the mesial temporal lobe, or the cingulum. Factor analysis provides statistical methods for evaluating patterns of cerebral changes in regional glucose uptake. Method: In 109 patients with MCI or mild AD cerebral metabolic rates were determined using positron‐emission tomography with [18F] deoxyglucose. According to the analyses of the scree plot factor analysis with VARIMAX rotation was used to identify underlying dimensions in 34 cerebral sites involved in AM deterioration. Subsequently, the respective factor scores were correlated with AM performance of 22 patients, which was measured with a structured inventory assessing memories from primary school, early adulthood, and recent years. Result: Factor analysis identified seven factors explaining 69 % of the variance ("frontal cortex, " "mesial temporal substructures", "cingulum", "occipital cortex", "left temporo‐prefrontal areas", "anterior cingulum", "right temporal cortex"). Relative to controls, AD patients showed significantly lower values on the factors "frontal cortex" and "mesial temporal substructures". The factor "mesial temporal substructures" was significantly correlated with both, episodic memories and personal semantic knowledge. Conclusion: Interestingly, changes of the mesial temporal substructures were correlated with both semantic and episodic AM. These findings don't necessarily contradict the multiple trace hypothesis as our sample only comprised patients with MCI or very mild AD for whom the relative preservation of semantic relative to episodic AM may not apply. In conclusion, our findings underline the importance of functional mesial temporal lobe changes in AD associated AM deficits.